Kulturna dediščina prihodnosti - Leskovar Polanič, Mateja (knjige, 2024)
Our idea was that we gather different countries around very interesting and important topic. We worked together in a project that we named Kulturna dediščina prihodnosti - Cultural heritage with modern touch. This subject is very wide and we hope, that with this project we will find those few important topics and discus them, write and talk about them and what is more, spread our knowledge to young people. Our aim was to keep some of those topics of cultural heritage of our countries preserved for our heirs, who will cherish them and take care of them. We tried to add some modern touch to make it more interesting for the youth and to make sure our heritage is not forgotten.